A universal method for improving the dynamical degradation of a digital chaotic system. (2nd July 2015) - Liu, Lingfeng; Miao, Suoxia
Abstract: Trying to generate a chaotic signal on a computer (or a finite precision machine) will lead to dynamical degradation of chaotic properties. In this paper, we use a variable function to replace the input variable of the chaotic system, which does not change the original chaos equation. We show that our new system has the properties of sensitive dependence on initial conditions and transitivity, and when the system is running on the finite precision device, the dynamical degradation has been greatly improved compared to the original digital chaotic system. Our method is universal, can be easily used in all the digital chaotic systems and is more efficient than the other frequently used methods in the overall characteristics.